Data Document Image Binarization for Preserving Historical: A Review - Bansinge, Bharti; Pateriya, RK (International Journal of Computer Sciences and Engineering, 2025)
The basic requirement of physical document analysis system is to digitalize the physical document. Recently number of researcher presented numerous techniques that can vary in sensitivity, quality and some more control parameters. Document binarization plays an important role in preserving the historical documents. The document image binarization focuses on extracting the text and background of the image. In doing this the edge detection approach also play the crucial role. This paper presents general review on the various approaches of document binarization. Various edge detection approaches are also been discussed. In addition various available data sets for image binarization developed in Document Image Binarization Contest (DIBCO) 2009 and Handwritten Document Image Binarization Competition (H-DIBCO) 2011 has also discussed.